Estimating Indexes of Coincident and Leading Indicators : An Application to Jordan - Mongardini, Joannes (IMF Working Papers; Working Paper, 2003)
The analysis of coincident and leading indicators can help policymakers gauge the short-term direction of economic activity. While such analysis is well established in advanced economies, it has received relatively little attention in many emerging market and developing economies, reflecting in part the lack of sufficient historical data to determine the reliability of these indicators. This paper presents an econometric approach to deriving composite indexes of coincident and leading indicators for a small open economy, Jordan. The results show that, even with limited monthly observations, it is possible to establish meaningful economic and statistically significant relations between indicators from different sectors of the economy and the present and future direction of economic activity.